Instalasi Berbasis Sensori Audio Sebagai Alat Permainan Anak untuk Menunjang Kegiatan Wisata Di Kampung Keranggan Tangerang Selatan - Ridzqo, Intan Findanavy; Refranisa, Refranisa; Hakim, Abi Maulana (Universitas Nusantara PGRI Kediri, 2022)
Kampung Keranggan located on the banks of the Cisadane River, is a pilot project of a tourism village in South Tangerang. However, both as a settlement and a place frequently visited by families, this kampung does not yet have a children playground. This space is very important, especially when an educational function is added to it. The vast landscape in this kampung is available and some area could be designed as a children playground equipped with installation to play. In this paper, the community engagement service activity is to design and to implement children's play installations, also served as educational facilities, namely tubulum and xylophone. Both are percussion instruments to train children’s audio sensory. These installations are made of PVC pipe and some household cutleries added on xylophone. This activity was begun with field observations and discussions with the management, making a digital installation design, making installation components in the workshop, and assembling and placing the installation on site. The principle of the installation design is to use materials that are easy to obtain and assemble, and are light in weight. These installations support tourist attraction activities in Keranggan Village and encourages children to play because this installation is placed in strategic place so visitors can easily play it and children are attracted because of its unique shape.